Formation of thin film Cr-N composites under ion bombardment at low rates of chromium deposition - Guglya, A.; Litvinenko, M.; Marchenko, Y.; Vasilenko, R. (Вопросы атомной науки и техники, 2006)
One of peculiar features of the IBAD technology consists in that the damage level and concentration of implanted ions are
distributed nonuniformly in the depth of deposited material. The calculations, we have done earlier [1], showed that the highest
degree of nonequilibrium is realized in the first 50 nm of a coating. However, just in this thickness the nucleation and formation
of the material structure is observed. The peculiarities of chromium coating formation without assisted irradiation and under
bombarding with nitrogen ions having the energy of 30 keV were studied. The rates of chromium deposition were low, 0,05…0,1
nm/s. During the experiment the vacuum was maintained at a level of 4·10⁻³ Pa and was determined, in main, by the content of nitrogen
molecules arriving from the discharging chamber of the ion source. The thickness within the range from 3 to 10 nm was
investigated. The results have shown that at the earliest stages of the film growth solely chromium nitride CrN is formed. Sizes
of visible nuclei are in the range from 1 to 4 nm, and their density is 1…3·10¹²cm⁻²
. As the film thickness increases, the nuclei are
growing, then their coalescence occurs and a uniform coating is formed. Chromium deposition without irradiation, but at the
same nitrogen pressure, resulted in formation of chromium hcp structure with the following crystallographic parameters: a = 0,315 nm; c = 0,492 nm. The grain size was 3…4 nm. After reaching the coating continuity, the hcp structure was transformed
into the bcc structure with the parameter a = 0,261 nm. Проведено сравнительное исследование начальных стадий формирования хромового покрытия в условиях бомбардировки ионами азота с энергией 30 кэВ и без ассистированного облучения, но при повышенном содержании азота в рабочей камере. Скорости осаждения были выбраны небольшими – 0,05...0,1 нм/с. Вакуум в камере был на уровне 4•10⁻³ Па и определялся в основном азотом, который напускался в разрядную камеру ионного источника. Толщина исследуемых объектов была в интервале 3…10 нм. Результаты показали, что при ионной бомбардировке происходит образование нитрида хрома CrN, начиная с самых ранних стадий роста пленки. Размер видимых зародышей находится в диапазоне 1…4 нм, плотность – 3•10¹² см⁻². С увеличением толщины пленки происходит коалесценция малых зародышей, образование свободных зон и зарождение на них новой популяции зерен. Осаждение хрома без ионного облучения приводит к формированию ГПУ-структуры с параметрами решетки а=0,315 нм и с=0,492 нм. При достижении сплошности у пленки происходит трансформация ГПУ-структуры в ОЦК с параметром а=0,261 нм. Проведено порівняльне вивчення початкової стадії формування хромового покриття в умовах бомбардування
іонами азоту з енергією 30 кеВ та без асистуючого опромінення, але при підвищеному тиску азоту. Швидкості
осадження були підібрані невеликі – 0,05…0,1 нм/с. Вакуум у камері був на рівні 4·10⁻³ Па та обумовлювався азотом,
який напускався в розрядову камеру іонного джерела. Товщина досліджених плівок – 3…10 нм. Результати показали, що
при іонному бомбардуванні має місце створення нітриду хрому CrN починаючи з самих початкових стадій. Розмір
зародків знаходиться у діапазоні 1…4 нм, щільність – 3·10¹² см⁻². Зі збільшенням товщини має місце коалесценція зародків, створення вільних зон та зародження на них нової популяції зерен. Осадження хрому без іонного опромінення
призводить до формування ГПУ-структури хрому з параметрами гратки а=0,315 нм та с=0,492 нм. При появленні сполошної плівки має місце трансформування ГПУ-структури у ОЦК з параметром а=0,261нм.